A Practice-based Study of Chinese Students’ Learning - Putting Things Together - Xu, Jinqi (Journal of University Teaching and Learning Practice, 2019)
This paper investigates Chinese students’ learning experience in the business Faculty of an Australian university. Chinese students are often characterized as “rote learners” or stereotyped as “reduced Other”. Areas of concern are limited to addressing the differences in learning styles, language, and sociocultural barriers. However, learning occurs in many forms. There is an absence of discussion about what practices Chinese students use in order to learn. Based on practice-based theory, a longitudinal ethnographic study of the journeys of five students was traced and investigates what practices Chinese students use in the learning and how these students “put things together” in the journey. This paper reports on two of the five students from the larger study. In particular, this article brings attention to the students’ everyday life and insights into their doings, sayings, and relatings between people, other beings and material artefacts. Chinese students’ learning involves foreground entanglements, co-construction, and relationality of practices from both educational and sociocultural perspectives. This paper provides new insights about Chinese students’ learning and encourages academics and institutions to be aware of the impact of their practices and to deepen their understanding of the complexities of Chinese students’ learning.